SIFAT FUNGSIONAL DAN FISIKO KIMIA DEDAK PADI TERSTABILISASI GELOMBANG MIKRO SELAMA PENYIMPANAN (The Functional and Physicochemical Properties of Stabilized Rice Bran with Microwave During Storage) - I Wayan Sweca Yasa; Agustono Prarudiyanto; Soegeng Prasetyo (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Rice bran is a by-product of rice milling industry, which contains considerable amount of protein, fat, carbohydrate and minerals. The aim of this study was to investigate the change of functional and physochemical properties of stabilised rice bran with microwave during storage. In this study, functional and physicochemical properties (including water and oil adsorption, emulsion capasity, foam stability and colour characteristics of rice bran obtain from heating (with microwave and without heating), packaging (with vaccum and without vaccum) and storing the rice bran for 0, 2, 4, 6, 8, 10, and 12 weeks on ambient temprature. The results showed that interaction between heating, packaging and the length of storage had affect on water adsorption, but did not have affect on oil absorption, emulsion and foam capasity of rice bran. The L and a value of rice bran was effected by the interaction between heating, packaging and the length of storage, however the b value, and Hue of rice bran was not effected. The rice bran with 3.42 ± 0.08% (g/g) which obtained from microwave heating, vaccum packaging and stored for 12 weeks had the highest amount of water adsorption. Oil adsorption capasity ranged from 6.73 ± 0.11% to 9.5 ± 0.48% for rice bran with microwave heating, vaccum packaging and 12 weeks of storage. The highest L and a value rice bran that was obtained from heating with microwave and without vaccum packaging was 76.02 ± 1.33 and 3.90 ± 0.04, respectively. The b value of rice bran ranged from 21.0 ± 0 to 22.80 ± 0.32 and Hue ranged from 80 ± 0.23 to 82.6 ± 0.37. Keywords: rice bran, microwave, packaging, storage, vaccum ABSTRAK Dedak padi merupakan hasil sampingan industri penggilingan padi, yang banyak mengandung protein, lemak, karbohidrat dan mineral. Penelitian ini bertujuan untuk mengetahui perubahan sifat fungsional dan fisikokimia dedak padi yang distabilisasi dengan gelombang mikro selama penyimpanan. Sifat fungsional dan fisikokimia dedak padi yang ditelaah meliputi daya serap air dan minyak, kapasitas emulsi, kapasitas buih dan karakteristik warna dedak padi yang diperoleh dengan pemanasan gelombang mikro dan tanpa pemanasan, dikemas vakum dan tanpa vakum, dan disimpan selama 0, 2, 4, 6, 8, 10 dan 12 minggu pada suhu kamar. Hasil penelitian ini menunjukkan bahwa interaksi antara pemanasan, pengemasan dan lama penyimpanan berpengaruh terhadap daya serap air, namun tidak berpengaruh terhadap daya serap minyak, kapasitas emulsi dan kapasitas buih dedak padi. Nilai L dan a dedak padi dipengaruhi oleh interaksi antara pemanasan, pengemasan dan lama penyimpanan, namun nilai b dan Hue dedak padi tidak terpengaruh. Daya serap air dedak padi sebesar 3,42 ± 0,08% (g/g) yang diperoleh dari pemanasan gelombang mikro dan pengemasan vakum serta disimpan selama 12 minggu merupakan yang tertinggi. Daya serap minyak dedak padi berkisar antara 6,73 ± 0,11% sampai dengan 9,5 ± 0,48%. Nilai L dan a tertinggi dedak padi diperoleh dari perlakuan pemanasan dengan gelombang mikro dan pengemasan tanpa vakum, yaitu berturut-turut sebesar 76,02 ± 1,33 sampai dengan 3,90 ± 0,04. Nilai b dedak padi yang dipanaskan dengan gelombang mikro dengan pengemasan vakum dan tanpa vakum berkisar antara 21,0 ± 0 hingga 22,80 ± 0,32, sedangkan Hue dedak padi berkisar antara 80 ± 0,23 hingga 82,6 ± 0,37. Kata kunci: dedak padi, gelombang mikro, pengemasan, penyimpanan, vakum